Pengaruh Penambahan Jamur Tiram (PLEUROTUS SP.) Terhadap Nilai Komposisi Kimia Dan Organoleptik Bakso Ayam Broiler - Ria Harmayani; Nefi Andriana Fajri (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Experimental research aimed to determine the effect of the addition of oyster mushrooms on the chemical composition and organoleptic value of broiler chicken meatballs. The research was corried out for 4 months from July to October 2020. The making of broiler chicken meatballs and organoleptics tests was carried out at the Laboratory of the Faculty of Animal Science UNW Mataram and chemical composition analysis was carried out at the INMT Laboratory of Mataram University. The research design used was a completely randomized design with 4 treatments, namely the addition of oyster mushrooms as much as 0%, 10%, 20% and 30% of the weight of chicken meat and each treatment there were 5 replications. The data from the research on the chemical composition of chicken meatballs were analyzed using variant analysis and continued with the LSD test and the organoleptic values were obtained using a hedonic scale from 30 panelists who were somewhat trained as replication, then analyzed using the Friedman Test. The analysis of variance result showed that the addition of oyster mushrooms in broiler’s chicken meatball dough had a very significant effect (P >0.01) on the value of chemical composition, namely moisture, ash, fat, fiber and protein content and had a significant effect (P>0.05) organoleptic values are colour preference, taste and aceeptance of meatballs, but it has no significant effect (P< 0.05) on the preference for aroma and texture of meatballs. The formulation of addition oyster mushrooms to broiler chicken meatballs based on the chemical composition value is the addition of 10% oyster mushrooms containing the highest protein of 8.51±0.014%, when compared to the addition of mushroom addition 0%, 20% and 30% and has met Indonesian National Standard for combination meatball and can be recomended for as nutritional terapy in the midst of the Covid-19 pandemic. Based on the organoleptic value, the formulation of broiler chicken meatballs with the addition of oyster mushrooms as much as 30% can provide higher organoleptic (colour, taste and acceptability) when compared to the addition of 0%, 10% and 20%.